Application of the Traditional Snakes and Ladders Game as an Indonesian Language Learning Media to Train Students' Language Skills in Elementary Schools - Fadiah Fahrunnisah; Wahidullah Enayat; Abdul Wajid Fazil (Balai Publikasi Indonesia, 2025)
In learning Indonesian, there are four good language skills that every student must have. Good language skills are one of the most important things in everyday life, so students should not only be taught about the theory conveyed through teacher explanations, it can make the learning atmosphere boring and the learning atmosphere less active, but they should also Teachers can make learning and learning models more effective so that they master, understand and can help train their language skills. Researchers here use literature study methods which require a deep thought process and insight. Namely by collecting data specifically through gathering information from books, trusted written sources related to the topic being researched, journals, and scientific publications. The data source used was obtained indirectly. One example of innovation that can help Indonesian education is using simple learning media based on Snakes and Ladders. The Snakes and Ladders learning media is a learning media that is neatly arranged and in its use it uses the Snakes and Ladders game pattern in general, making it easy for students to adapt to this learning media. Making Snakes and Ladders learning media can be an alternative in the learning process so that it can create a teaching and learning atmosphere that is more varied, more enthusiastic, and more active. One of the learning media is Snakes and Ladders, which can be used in the teaching and learning process to train students' abilities in their language skills in Indonesian language lessons. This game can be a forum or place that students can use to play and learn.